Traumatic Diaphragmatic Rupture: A Case Report - KC, Sudeep; Acharya, Riwaz (Nepal Medical College Journal, 2025)
Traumatic diaphragmatic rupture is a rare but serious condition, often linked to high-velocity injuries, predominantly located on the left side. Traumatic ruptured diaphragm is a surgical emergency with a high mortality rate, and diagnosing it can be challenging. This report discusses a 48-year-old male who initially presented to the Emergency Department (ED) with complaints of chest pain and shortness of breath after a fall. Initial chest X-ray showed elevated right diaphragm and basal atelectasis, while Computed Tomography (CT) scan showed right sided diaphragmatic rupture with intra thoracic liver herniation and multiple bone fractures. Diaphragmatic rupture was later confirmed during surgery and underwent closure of the defect. This particular case underscores the importance of early detection and immediate treatment for traumatic ruptured diaphragm. This case report delves into an instance of right sided traumatic diaphragmatic rupture in a polytrauma patient. Radiological imaging not only plays a crucial role in confirming the diagnosis but also guides treatment planning, including the consideration of other associated injuries.